International tourism as one of the directions of implementation of inclusive development model - Kaliyaskarova, B.А.; Makenova, G.U.; Kargabayeva, S.T.; Akhmetova, K.I. (BUKETOV BUSINESS REVIEW, 2023)
Object: Solving the problems of tourism development at the territorial level, to ensure the concept of sustainable and inclusive development through the interconnected achievement of such indicators as ecology, social and economic and other problems. Methods: Application of sustainability indicators to use the arithmetic mean of the normalized values of the indicators for each area. The priority of each indicator is calculated based on its share in the sum of the values of the proposed indicators. Correlation analysis was used to determine the degree of correlation between the indicators of sustainable development of the Republic of Kazakhstan and the territories under consideration. For this, Pearson's linear correlation coefficients were calculated. Findings: The results of the integrated indicators of sustainable development in the context of the regions under consideration show that the sustainability of the development of the Almaty region, the city of Almaty and the East Kazakhstan region is closely related to the integrated sustainability of tourism activities. In addition, since the tourism sector is closely related to other activities, the management of the tourist area on the basis of an integrated sustainable development model contributes to the stability of the local environment and the formation of synergies in the economic, social and technological spheres. Conclusions: Priority weights were defined as the actual share of the absolute value of each resistance indicator to the sum of the absolute values of all six indicators. The values of integral indicators of sustainable development of the regions under consideration and the Republic of Kazakhstan were determined by the formula of sustainability indicators.